EFFECT OF TALENT MANAGEMENT, WORK LIFE BALANCE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AND JOB SATISFACTION AS INTERVENING VARIABLES IN PT. TUV NORD INDONESIA - Eko Wahyudi; Masydzulhak Djamil; Ahmad Badawi saluy; Novawiguna Kemalasari; Abdul Bari (Dinasti International Journal of Management Science, 2022)
Talent management, Work Life Balance, organizational commitment, Employee Performance and job satisfaction in an organization are very important areas in the workplace. This can help organizations improve and utilize their human resource capacities. Employee performance at PT. TUV NORD Indonesia is very important in determining success in achieving company goals. Based on the results of observations and initial interviews with the Management regarding staff performance and job satisfaction, as well as data obtained from the Human Resource Department of PT. TUV NORD Indonesia, several phenomena were found. Based on this, the author conducted research with the research design used in this study is quantitative with a correlational approach. The results of the study show that Talent management, Work Life Balance, organizational commitment affect job satisfaction and employee performance at PT. TUV NORD Indonesia.